Characterization of telomere length in Agerolese cattle breed, correlating blood and milk samples. (1st July 2022) - Iannuzzi, Alessandra; Albarella, Sara; Parma, Pietro; Galdiero, Giacomo; D'Anza, Emanuele; Pistucci, Ramona; Peretti, Vincenzo; Ciotola, Francesca
Abstract: Studies into telomere length in cattle are relatively recent and have focused mainly on the Holstein Friesian cattle breed, making it arduous to evaluate the correlation with ageing due to the early age of culling in this breed. Telomere length provides information about the productive lifespan and the quality of farm management, complying with the 'One Health' approach. This study evaluated telomere length in Agerolese cattle, an autochthonous dairy breed characterized by a long productive lifespan (13 years). Multiplex quantitative PCR estimated telomere length in DNA extracted from blood and milk matrices. Interestingly, the results showed longer telomeres in Agerolese (compared to the Holstein Friesian cattle control group), with a negative correlation between telomere length and increasing age and a synchronous trend between blood and milk samples, with a positive correlation between them.